Changes in the Structure of the Chromosomes of Lymphocytes during Persistent Infection in Children - V. S. Sevryukova; E. O. Khalturina; P. E. Dobryakov; V. S. Kozhevnikov (Детские инфекции (Москва))
Children with chronic diseases of respiratory tract were investigated for IgM and IgG serum antibodies to viruses (Herpes simplex virus, Epstein-Barr virus, Cytomegalovirus) and bacteria (Chlamydia trachomatis + pneumoniae, Mycoplasma pneumonia) by ELISA and for telomere length of their lymphocytes by fluorescent hybridization in situ followed by flow cytomerty (FlowFISH). The purpose of the study was to compare the lymphocyte telomere length of these seropositive and seronegative children. Regression analysis and analysis of percent distribution relative to the regression line have compensated age differences between seropositive and seronegative groops and demonstrated shorter telomeres in lymphocytes of children those have serum antibodies to viruses in all combinations (including combinations with antibodies to bacteria) in contrast to seronegative children of the same age.